Evaluasi Penerapan Standard Operating Procedure-Good Agriculture Practice (SOP-GAP) pada Usahatani Padi Organik di Kabupaten Bantul - Sriyadi, Sriyadi; Istiyanti, Eni; Fivintari, Francy Risvansuna (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
Food security has meaning not only the availability of adequate food, but also providing security for producers and consumers and ensuring environmental sustainability for sustainable production. Organic farming systems are expected to solve the problem for realizing food security and enhancement of peoples welfare. The results of research indicated that, (1) The implementation level of Standard Operating Procedure-Good Agriculture Practice (SOP-GAP) of Organic Rice Farming in Bantul district was quite high, (2) The implementation level of SOP-GAP of Organic Rice Farming related to the availability of capital, the selling price and the purchase price of inputs (seeds and fertilizers), (3) The level of the farmers decision related to the implementation level of SOP-GAP of organic rice farming, and (4) development of organic rice farming required availability of sufficient capital. In this regard the government, particularly the agriculture authority and food security agency need to disburse or facilitate capital for farmers in revolving as well as low interest loans.